Analisis Pengendalian Kualitas Tray dengan Metode Basic Seven Tools dalam Upaya Meminimalisir Produk Reject pada PT XYZ - Hakika Syaula Nurrajab S.P; Ade Momon (Peneliti.net, 2022)
Intense competition between industries in the current era of globalization makes PT XYZ to be competitive at all times. Product quality is the main factor in competing. This study aims to look at quality control in the company and efforts to minimize product rejects using the basic seven-tool method. Several basic seven tools were used in this research to assist in data analysis. In the Pareto diagram, it can be seen that the thinning defect is the main defect in the low quality of tray products, with a percentage of 28.03%. In addition, the results of the p-control chart also show that there is still a lack of quality control in the company. A fishbone diagram is used to analyze the root cause of the problem. Suggestions for improvement that can be given for each problem that causes product rejects are to provide standardization in the production process so that the product produced is in accordance with the standards that have been set